Musikförderung als Instrument der Integration im Spannungsfeld zwischen Integrations-, Bildungs- und Kulturpolitik - Fröhlich, Beate (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2019)
In a time of an upswing of integration policy during the 2000s, a position was spread by cultural-political associations as well as on different political levels, according to which cultural expressions such as music have great potential for social integration. At the same time, migrants as (non-)users of cultural institutions were given more cultural-political focus. From an integration, cultural and educational policy perspective, it was examined to what extent music promotion contributes to social integration and how this is reflected in pro-motion policy. At first, based on a secondary analysis, the role of music in the context of migration and integration was analyzed. Political decision-making contents (subsidies, promotion goals) including implementation (support structures) and causes (support conception) at the federal level and at the level of federal provinces were analyzed on the basis of the policy cycle, from the point of view of integration and cultural policy. Cultural and integration concepts as well as application forms, funding guidelines and laws in the areas of cultural policy, intercultural policy and integration policy were analyzed. A coordinated approach to the challenges of integration in education, integration and cultural policies is not apparent. Fields of action, structures, goals, promotional items and the associated dependencies can not be clearly defined in the culture and integration concepts. The interdisciplinary approach has shown that the findings of the various fields of research (e.g. intercultural music pedagogy, organizational development) receive little attention from each other.

Ausgangspunkt der Untersuchung war die Feststellung, dass in einer Zeit des integrations-politischen Aufschwungs in den 2000er Jahren durch kulturpolitische Verbände sowie auf politischer Ebenen eine Position verbreitet wurde, wonach kulturelle Ausdrucksweisen wie Musik Potentiale zur gesellschaftlichen Integration aufweisen. Parallel gerieten Migranten als (Nicht-)Nutzer von Kultureinrichtungen in den kulturpolitischen Fokus. Aus integrations-, kultur- und bildungspolitischer Perspektive wurde untersucht, inwieweit Musikförderung zur gesellschaftlichen Integration beiträgt und wie sich dies in der Förderpolitik niederschlägt. Zunächst wurde auf Basis einer Sekundäranalyse hinterfragt, welche Funktionen Musik im Kontext von Migration und Integration zukommen. Im Rahmen einer Politikfeldanalyse wurden anhand des Policy Cycle aus Sicht der Integrations- und der Kulturpolitik politische Entscheidungsinhalte (Fördergegenstände, Förderziele) einschließlich Umsetzung (Förderstrukturen) und Ursachen (Förderverständnis) auf Landes- und Bundesebene analysiert. Dazu wurden Kultur- und Integrationskonzepte sowie Antragsformulare, Förderrichtlinien und Gesetze in den Bereichen Kulturpolitik, interkulturelle Kulturpolitik und Integration analysiert. Eine abgestimmte Herangehensweise an die Herausforderungen der Integration in der Bildungs-, Integrations- und Kulturpolitik sind nicht erkennbar. Handlungsfelder, Strukturen, Ziele, Fördergegenstände und die damit verbundenen Abhängigkeiten sind in den Kultur- und Integrationskonzepten nicht eindeutig abgrenzbar. Durch die interdisziplinäre Herangehensweise wurde gezeigt, dass die Erkenntnisse der verschiedenen Forschungsfelder (z.B. interkulturelle Musikpädagogik, Organisationsentwicklung) in den jeweils anderen kaum Beachtung finden.
Music promotion as a means of integrating migrants in the context of integration policy, education policy and cultural policy
Keywords: Integration; Integration Policy; Music Promotion; Intercultural Education; Cultural Policy; Integration; Interkulturelle Erziehung; Kulturpolitik; Integrationspolitik; Musikförderung; 780 Musik